Design, synthesis, antifungal activity and molecular docking of ring‐opened pimprinine derivative containing (thio)amide structure. Issue 6 (21st February 2023) - Cheng, Lan; Liu, Jing‐Rui; Liu, Jia‐Mu; Guo, Dale; Deng, Fang; Bian, Qiang; Zhang, Haifeng; Han, Xinya; Ali, Abdallah S; Zhang, Wei‐Hua; Zhang, Ming‐Zhi; Gu, Yu‐Cheng
Abstract: BACKGROUND: To obtain new environmentally friendly fungicides, we used the natural product pimprinine as the lead compound, and designed and synthesized two series of ring‐opening derivatives of pimprinine containing amide/thioamide. We then studied their antifungal activity against six common plant pathogenic fungi in vitro. RESULTS: Most of the target compounds have good antifungal activity against six important plant pathogenic fungi in vitro. At a concentration of 50 μg ml −1, compound 3o showed prominent antifungal effects on Alternaria solani and Rhioctornia solani, with inhibition rates of 91.8% and 97.4%, and a 50% effective concentration (EC50 ) of 6.2255 and 0.6969 μg ml −1 respectively. The EC50 of compound 3o against Alternaria solani was significantly lower than that of boscalid (13.0380 μg ml −1 ) and flutriafol (11.9057 μg ml −1 ). In addition, compound 3o had good antifungal activity against Sclerotinia sclerotiorum, cucumber powdery mildew, cucumber Botrytis cinerea and Phytophthora capsici in vivo; the antifungal activity of compound 3o against cucumber Botrytis cinerea is 91.7%. At the same time, docking results for highly active compound 3o with the presumed target succinate dehydrogenase and the molecular docking prediction scores of all compounds further indicate its possible antifungal activity mechanism. CONCLUSION: The designed and optimized derivative 3o of ring‐opening pimprinine has good antifungal activity and can be used as a new antifungal drug for further research. © 2023 Society of Chemical Industry. Abstract : Thirty‐four novel indole (thio)amides were designed and synthesized as pimprinine ring‐opening derivatives, and their antifungal activity in vitro and in vivo was assayed for the first time. Molecular docking scores and actual activity predicted the mode of action. Compound 3o is identified as a promising lead for the development of new fungicide.